Evaluation of the Training Program for Homeless and Beggars at the Social Rehabilitation UPTD Bina Karya Pasuruan: A Public Policy Perspective - Agung Purnomo; Ika Devy Pramudiana; Nihayatus Sholichah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study evaluates the effectiveness of vocational training programs for homeless persons and beggars at the UPT Rehabilitasi Sosial Bina Karya Pasuruan, East Java, Indonesia, through a public policy perspective. Drawing on Edi Sutrisno’s (2007) effectiveness indicators—comprising program comprehension, targeting accuracy, time management, goal attainment, and visible behavioral change—the research employs a qualitative descriptive method. Data were collected through participatory observation, in-depth interviews with nine key subjects (social rehabilitation staff, social workers, and skills instructors) and four beneficiary informants, and documentary analysis. The findings reveal that the program has not yet reached an effective level of implementation. Key inhibiting factors include mismatches between beneficiaries’ backgrounds and available skill tracks, outdated program design, low intrinsic motivation among clients, and limited post-rehabilitation follow-up. Supporting factors include the availability of qualified instructors, adequate facilities and infrastructure, and a generally high willingness among beneficiaries to participate in activities. The study concludes that a policy redesign is necessary, incorporating needs-based program planning, enhanced motivational interventions, updated curriculum content aligned with current labor market demands, and strengthened inter-agency collaboration. These findings contribute to public policy discourse on social welfare program evaluation and offer practical recommendations for government rehabilitation institutions.